Visit Improvement Effort of Inpatient Obstetrics and Gynecology in RSIA Kirana Sidoarjo Using Blue Ocean Strategy - Eny Lusiadewi; Whidya Utami (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The purpose of this study is to identify and analyze innovation efforts to increase inpatient obstetrics and gynecology at the Kirana Sidoarjo Mother and Children Hospital (RSIA) using the Blue Ocean Strategy. Design/methodology/approach: The design/methodology/approach used in this research is descriptive qualitative research with a case study. This research is directed to reach a strategic decision through the blue ocean strategy at RSIA Kirana Sidoarjo which is supported by analysis and clear arguments. The search for untapped market space makes it necessary to first configure the logic of the Blue Ocean Strategy. Findings: The results showed that innovation efforts to increase inpatient visits to obstetrics and gynecology at the Kirana Sidoarjo Mother and Child Hospital (RSIA) using the Blue Ocean Strategy were by increasing digital marketing factors, quality of human resources and services, integrated hospital information systems, Hospital service innovation, Quality control/assurance. brand and the creation of Complimentary Service factors, After sales service. Paper type: Research paper